An unusual cause of apparent rebreathing associated with anaesthesia delivered by a coaxial circle breathing system. Issue 2 (6th December 2016) - Goosen, Leonard; Hall, Alexander J; Elsey, Chris; Uncles, David R
Summary: This case report describes an unusual case of equipment failure resulting in the appearance of a rebreathing artefact on an associated capnography waveform trace that we believe has not been previously reported. The rebreathing artefact occurred with a single‐use coaxial circle breathing system which included an integral gas sampling line within the expiratory limb. Close examination of the system revealed a defect in the sampling line resulting in gas sampling predominantly from the expiratory limb of the circle system. This defect was not detectable by either the anaesthetic machine automated self‐testing cycle or visual inspection of the breathing system.